Combined exposure to mixed brominated flame retardants on obstructive sleep apnea syndrome in US adults - Junping Liu; Zhaoyue Liu; Xinru Liu; Nan Wang; Lin Wu; Xiaoxue Xu; Wei Liu; Yajie Feng; Huanyu Zhang; Yue Zhou; Xinle Yin; Yaping Liu; et al. (BMC Public Health)
Abstract Background Accumulating research highlights that exposure to serum brominated flame retardants (BFRs) may elevate health risks. The effects of serum BFRs, both alone and in combination, on obstructive sleep apnea syndrome (OSAS) have not been thoroughly studied. Our main goal was to examine the association between individual and mixtures of serum BFRs and OSAS risk. Methods Data from the National Health and Nutrition Examination Survey (NHANES) were employed, including 1,341 participants. We included participants with full details on OSAS, covariates, and 7 types of serum BFRs (PBDE28, PBDE47, PBDE99, PBDE100, PBDE153, PBB153, and PBDE209). To investigate the OSAS risk with BFRs exposure, multivariate logistic regression, weighted quantile sum (WQS) regression, quantile g-computation (QGC), Bayesian kernel machine regression (BKMR) models, and restricted cubic splines (RCS) were implemented. Results Serum BFRs, including PBDE28, PBDE47, PBDE99, PBDE100, and PBB153, showed positive correlations with the OSAS risk. The toxic effect of serum BFRs co-exposure on OSAS risk was consistently demonstrated through the results of WQS regression, QGC and BKMR models. PBB153 was determined to be the most weighted BFRs. Additionally, RCS regression model also verified the strong non-linear relationship that existed between OSAS risk and PBB153. Conclusions Findings of the study prove that BFRs co-exposure exerts a deleterious effect on OSAS risk. Future large-scale prospective investigations and experimental studies are desirable to confirm these findings.